PENGARUH PENGGUNAAN ICE BREAKING DALAM PENINGKATAN KETERAMPILAN PROSES SAINS FISIKA SISWA SMP NEGERI 5 ANGKOLA TIMUR - Nasution, Eni Sumanti; Putri, Ramita; Dewi, Nova Christina (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
This study sought to examine the impact of ice breaking techniques on the ability of students at SMP Negeri 5 Angkola Timur to comprehend physical science information. The participants involved in this study were exclusively students from SMP Negeri 5 Angkola Timur. The research utilized cluster sampling, selecting two classes (VII1 and VII2), each comprising thirty students. A quasi-experimental design was employed, distinguishing between an experimental class and a control class. A multiple-choice test comprising Twenty questions on science process skills served as the research instrument. Prior to the study, The exam questions' reliability and validity were evaluated. Validity scores were obtained from students before subjecting the data to analysis through homogeneity tests, normality tests, and t-tests in both the pretest (prior to treatment) and posttest (following treatment) classes. The results indicated that the utilization of ice breaking significantly influenced the physical science process skills of students in the posttest class at SMP Negeri 5 Angkola Timur.